Passivation strategies in lead-free perovskite solar cells: Towards efficient and stable photovoltaic devices - Aasim Ahmed Abdelghafar; Ayman Mdallal; Mohamed Adel Allam; Hamad Al Ali; Abdul Hai Alami; Mohammad Ali Abdelkareem; A.G. Olabi (Energy Nexus, 2025)
The development of perovskite solar cells (PSCs) technology has been accelerating tremendously over the past decade. With the recent approved world-record power conversion efficiency (PCE) of PSCs of 27 %, perovskites have become the first solution-processed technology to surpass the performance of thin-film and multi-crystalline silicon. In order to implement this technology on a large scale, two primary limitations that must be dealt with are toxicity of lead (Pb) and perovskite stability. Despite the fact that Pb is a de facto material in third generation photovoltaic devices, it is highly recommended for health, safety and environmental necessity to explore alternatives that still possess the unique optoelectronic characteristics of lead halide perovskites. Pb-free perovskite materials have been gaining extensive attention as promising candidates to solve the toxicity issue. More importantly, Passivation plays a critical role in enhancing the performance and stability of Pb-free perovskite solar cells by mitigating defect-induced non-radiative recombination at interfaces and grain boundaries. Effective passivation strategies significantly improve carrier lifetimes and reduce energy losses, which are essential for achieving better PCEs. Therefore, this review thoroughly discusses the advances of various passivation additives in enhancing photoelectric efficiency as well as the environmental stability of Pb-free PSCs. Additionally, the contribution of passivation materials in the mitigation of different drawbacks presented on perovskites, including defect density, charge carrier recombination rate and Sn2+ oxidation has been highlighted, paving the way to push the limits of lead-free solar devices even further.